Screening of the Dichloromethane: Methanolic Extract of Centella asiatica for Antibacterial Activities against Salmonella typhi, Escherichia coli, Shigella sonnei, Bacillus subtilis, and Staphylococcus aureus - Berick Moturi Sieberi; George Isanda Omwenga; Rachael Kitondo Wambua; Judith Chemutai Samoei; Mathew Piero Ngugi (The Scientific World Journal)
Bacterial infections are responsible for a large number of deaths every year worldwide. On average, 80% of the African population cannot afford conventional drugs. Moreover, many synthetic antibiotics are associated with side effects and progressive increase in antimicrobial resistance. Currently, there is growing interest in discovering new antibacterial agents from ethnomedicinal plants. About 60% of the population living in developing countries depends on herbal drugs for healthcare needs. This study involved the screening of Centella asiatica commonly used by herbal medicine practitioners in Kisii County to treat symptoms related to bacterial infections. Standard bioassay methods were applied throughout the study. They included preliminary screening of dichloromethane: methanolic extract of Centella asiatica against human pathogenic bacteria including Salmonella typhi ATCC 19430, Escherichia coli ATCC 25922, Shigella sonnei ATCC 25931, Bacillus subtilis ATCC 21332, and Staphylococcus aureus ATCC 25923 using agar disc diffusion, broth microdilution method, and time-kill kinetics with tetracycline as a positive control. Phytochemical screening was carried out to determine the different classes of compounds in the crude extracts. Data were analyzed using one way ANOVA and means separated by Tukey’s test. Dichloromethane: methanolic extract of Centella asiatica was screened against the selected bacterial strains. Time-kill kinetic studies of the extracts showed dose- and time-dependent kinetics of antibacterial properties. Phytochemical screening of the DCM-MeOH extract revealed the presence of alkaloids, flavonoids, phenolics, terpenoids, cardiac glycosides, saponins, steroids, and tannins. The present study indicates that the tested plant can be an important source of antibacterial agents and recommends that the active phytoconstituents be isolated, identified, and screened individually for activities and also subjected further for in vivo and toxicological studies.